2021
DOI: 10.1371/journal.pntd.0009300
|View full text |Cite
|
Sign up to set email alerts
|

Early control of viral load by favipiravir promotes survival to Ebola virus challenge and prevents cytokine storm in non-human primates

Abstract: Ebola virus has been responsible for two major epidemics over the last several years and there has been a strong effort to find potential treatments that can improve the disease outcome. Antiviral favipiravir was thus tested on non-human primates infected with Ebola virus. Half of the treated animals survived the Ebola virus challenge, whereas the infection was fully lethal for the untreated ones. Moreover, the treated animals that did not survive died later than the controls. We evaluated the hematological, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Moreover, control animals generated an excessive inflammatory response punctuated by substantial upregulation of genes encoding cytokines and chemokines and those important for neutrophil activation and function. This is in line with previous reports of neutrophilia and cytokine storm following lethal challenge with both EBOV and MARV (8,12,16,27,(37)(38)(39)(40). Finally, robust induction of genes that play a role in wound healing was also detected in control animals, indicative of the coagulopathy that accompanies EVD and MVD (37,39,40).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, control animals generated an excessive inflammatory response punctuated by substantial upregulation of genes encoding cytokines and chemokines and those important for neutrophil activation and function. This is in line with previous reports of neutrophilia and cytokine storm following lethal challenge with both EBOV and MARV (8,12,16,27,(37)(38)(39)(40). Finally, robust induction of genes that play a role in wound healing was also detected in control animals, indicative of the coagulopathy that accompanies EVD and MVD (37,39,40).…”
Section: Discussionsupporting
confidence: 93%
“…However, NK cells may be a double-edged sword in the treatment of COVID-19, as it is one of the culprits in the development of cytokine storm syndrome, one of the most common causes of death in a new crown pneumonia [ 57 , 58 ]. In a recently published study, Reynard et al applied FVP to treat Ebola virus in non-human primates and concluded that the reduction of viral load by FVP in early treatment is associated with a reduction in the release of related cytokines including NK cells, greatly reducing the incidence of developing cytokine storms, thereby reducing disease severity [ 59 ]. Interestingly, Ferri et al reported a significant rate of SARS-CoV-2 infection in patients with autoimmune systemic diseases compared to the general population, but these patients tended to have relatively benign outcomes after diagnosis of COVID-19, possibly because such patients are themselves taking immunosuppressive agents (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of immune response followed by overexpression later during infection has been linked to fatality in previous animal model and human studies 61 . High viral loads early during infection followed by sustained upregulation of immune signaling activity in Leydig cells is reminiscent of the so-called cytokine storm that has been reported in fatal cases of EVD, in which case the more moderate response observed in Sertoli cells may go some way to explaining their continued survival 62,63 . The Sertoli cells maintain an immune privileged niche in part through anti-inflammatory signaling, and this may explain our observations in the current study as well as the asymptomatic nature of persistent testicular EBOV infections 3,22 .…”
Section: Leydig Cells Overreact While Sertoli Cells Keep Calm and Car...mentioning
confidence: 99%
“…In this case, extended upregulation of the Hemostasis pathway may be a response mounted by Leydig and Sertoli cells in opposition to downregulation induced by EBOV. If this is the case, then hemorrhaging during EVD may be caused by an overly robust response by host cells, similar to the cytokine storm 62,63 .…”
Section: Leydig Cells Overreact While Sertoli Cells Keep Calm and Car...mentioning
confidence: 99%